Sound pressure level in the speech signal due to the use of a mask or face shield - Marsano Cornejo, María José.; Roco Videla, Ángel Gerardo.; Aguilera Eguía, Raúl Alberto.; Flores, Sergio V. (AG Editor, 2024)
Introduction: the use of masks and face shields became widespread during the COVID-19 pandemic, but their impact on vocal health, especially in those who use their voice as a work tool, is not yet fully studied. This study investigates the effect of different types of masks and face shields on the sound pressure level of the voice, with special attention to the risk of developing vocal pathologies. Methods: voice recordings were made of 18 participants (11 women and 7 men) in an audiometric booth, measuring the equivalent continuous sound pressure level (Leq) with a sound level meter. The results obtained with different types of masks (surgical, KN95, with transparent window) and a face shield were compared. Results: no significant differences were found in Leq between the groups with and without protective elements. However, it was observed that women tend to increase the intensity of their voice when wearing masks or face shields, which could lead to greater vocal effort and a potential risk of developing long-term vocal pathologies. Conclusions: Although the use of masks and face shields is necessary in certain contexts, it is important to consider the possible consequences for vocal health, especially in women. The use of non-verbal language is recommended to complement communication and avoid combining KN95 masks with face shields when not strictly necessary.
Nivel de presión sonora en la señal de habla debido al uso de mascarilla o escudo facial
Keywords: Face shield; Sound pressure level; Voice intensity; Máscaras